Judgements without trial in civil proceedings in Malaysia: a brief analysis on the burden of proof required - Haniwarda Yaakob, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Civil proceedings involve a complex procedure with various interlocutory applications before the matter is set for trial. Some of the interlocutory applications, namely applications to enter judgment in default, to strike out pleading and for summary judgment, may result in the plaintiff obtaining early judgment or disposal of the case without a full trial. Interestingly, these applications require a different burden of proof for the plaintiff to satisfy. This article seeks to explore the burden of proof necessitated in those applications in order to evaluate the likelihood of the plaintiff obtaining judgment without trial. In achieving this objective, the process of civil proceedings in Malaysia is briefly explained. This is followed by an analysis on the burden of proof required in the said applications. It is observed that although judgment in defaults or summary judgment may be entered against the defendant upon the plaintiff’s satisfaction of mere procedural requirements, it is equally ‘easy’ for the defendant to set aside or oppose such judgment or application. A conclusion can be derived that civil procedure in Malaysia allows the defendant a sufficient right or opportunity to have ‘his day in court’ by placing a low threshold for him set aside judgment in default or oppose summary judgment application. Further, it is also observed that a stringent burden of proof is needed for the plaintiff to be able to strike out the defendant’s defence and enter judgment on his behalf. This is, arguably crucial so as to cloth the defendant with the right to a fair trial which includes the right to be heard and present their cases sufficiently.